Penggunaan Strategi Pembelajaran Dan Lingkungan Sekolah Untuk Hasil Belajar Siswa - Supriyanto, M.Pd (STAI Kuala Kapuas, 2023)
The law on the educational system (No. 20/2003) stated, the purpose of national education developed the potential of students became human believers and devoted to Allah SWT, noble, healthy, knowledgeable, capable, creative, independent and institutionalized citizens who were democracy and responsible. The obsavavation found by researchers in MI Al-Amin Kapuas was two factors that inhibit the learning outcomes of Students, First, the use of learning strategies by the teacher, where teachers did not understand the differences in learning strategies, learning methods, learning techniques. Second, school environment factor. Dismissal of the school environment such as lack of information about the elements of the school environment. School activities and environmental events. Thus, researscher was interested in testing the hypothesis about whether there was a positive relationship from teacher learning strategies and the school environment with Student IPS learning outcomes in MI Al-Amin Kapuas. The purpose of this study is knowing significantly in the relationship of learning strategies by teachers and the school environment with the learning outcome of MI Al-Amin Kapuas. The research method uses causal survey with path analysis techniques included formulas by Henry E. Garret for data normality,, correlation of 'r' product moment for validity, alpha formula for reliability and final stage analysis techniques The data collection technique used a questionnaire as a primary instrument and secondary documentation instrument. The population of this study, all students of Mi Al-Amin Kapuas numbered 399 students. While the affordable population is 97 students. Determination of the number of samples used by Slovin's formula with 50 student probabilty techniques. Based on research findings on the relationship of teacher learning strategies and the school environment with the learning outcome of social studies students of Mi Al-Amin Kapuas, namely the positive relationship between the use of learning strategies by teachers and the school environment together with learning outcomes of learning. Thus, the higher the use of the learning strategy by the teacher and conducive to the school environment, the higher the learning outcomes of IPS students of Mi Al-Amin Kapuas. Conversely, the increasingly never uses learning strategies and not conducive to the school environment, lower than the learning outcomes of IPS students of Mi Al-Amin Kapuas students.